237 MEASURES OF NUTRITIONAL STATUS IN CHRONICALLY VENTILATED PRETERM LAMBS. (10th December 2015) - Anderson, D.; Moyer-Mileur, L. J.; Williams, M.; Dahl, M. J.; Albertine, K. H.
Abstract : Background: Preterm delivery interrupts the acquisition of nutrient stores that normally occurs during the later period of gestation. Energy and nutrient needs of preterm infants can be 20 to 300% greater than those of term infants. Little is known about the nutritional status or requirements of preterm lambs that are chronically ventilated. Therefore, we compared the nutritional status of chronically ventilated preterm lambs to term lambs. Hypothesis: We hypothesized that serum glucose and fructose concentrations differ between ventilated preterm lambs and normal term lambs. Methods: Plasma samples, obtained at 0, 24, 48, 72h of life from preterm lambs (n=21; delivered at ˜130d gestation) and term lambs (n=7; term gestation ˜147d), were analyzed by enzymatic assays to determine glucose and fructose concentrations. Preterm lambs were managed by conventional mechanical ventilation (CV) or nasal continuous positive airway pressure (nCPAP) for 24 or 72h. Orogastric feeding of ewe's colostrum was begun within 6h of life and advanced as tolerated. Dextrose infusion (D10-12.5%) was also provided to maintain serum glucose concentration. Dextrose load (g/kg/d) was calculated from 24h intakes. Term lambs nursed ad libitum. Results: No significant differences for glucose or fructose concentrations were found between preterm and term lambs (e.g., glucose at 24h: 172±87 mg/dL (preterm; X±SD) vs 138± 56 (term) at 24h of life). No significant differences for dextrose load were found between the two preterm lamb groups (e.g., at 72h: 41±23 g/kg/d for CV vs 41± 15 for nCPAP). Conclusion: Glucose and fructose nutritional status in preterm lambs was matched to that of term lambs. Whether protein and mineral status were maintained remains to be determined.